The effects of nitrogen fertilizer application on methane and nitrous oxide emission/uptake in Chinese croplands - Bin-feng SUN; Hong ZHAO; Yi-zhong LÜ; Fei LU; Xiao-ke WANG (Journal of Integrative Agriculture)
Abstract: The application of nitrogen (N) fertilizer to increase crop yields has a significant influence on soil methane (CH4) and nitrous oxide (N2O) emission/uptake. A meta-analysis was carried out on the effect of N application on (i) CH4 emissions in rice paddies, (ii) CH4 uptake in upland fields and (iii) N2O emissions. The responses of CH4 emissions to N application in rice paddies were highly variable and overall no effects were found. CH4 emissions were stimulated at low N application rates (<100 kg N ha−1) but inhibited at high N rates (>200 kg N ha−1) as compared to no N fertilizer (control). The response of CH4 uptake to N application in upland fields was 15% lower than control, with a mean CH4 uptake factor of −0.001 kg CH4-C kg−1 N. The mean N2O emission factors were 1.00 and 0.94% for maize (Zea mays) and wheat (Triticum aestivum), respectively, but significantly lower for the rice (Oryza sativa) (0.51%). Compared with controls, N addition overall increased global warming potential of CH4 and N2O emissions by 78%. Our result revealed that response of CH4 emission to N input might depend on the CH4 concentration in rice paddy. The critical factors that affected CH4 uptake and N2O emission were N fertilizer application rate and the controls of CH4 uptake and N2O emission. The influences of application times, cropping systems and measurement frequency should all be considered when assessing CH4 and N2O emissions/uptake induced by N fertilizer.